SEKOLAH UNGGULAN - Soehadi Widjaja (Sekolah Tinggi Teologi Duta Panisal, 2020)
Excellent school is a school that is able to bring their students excel intellectually, emotionally and spiritually. School excels in general emphasizes the quality of the students, so that later they can compete in the global life on earth. Superior school generally have specific characteristics, including excellent student, teacher professional, disciplined, dedicated, intelligent, able to create designs, strategies, models and methods of teaching, friendly and can mingle with fellow teachers and students. The process of learning to walk fun run, the principal good and able to act as a good manager. Managing superior schools should be run professionally, including criteria for teachers should be in accordance with the Indonesian Government Regulation No. 19 of 2005 on National Education Standards (NES).